Body image and healthy lifestyle behaviors of university students - Bednarzyk, Michele S.; Wright, Tracy L.; Bloom, Kathaleen C. (International Journal of Advanced Nursing Studies, 2013)
Background: Body image, one’s perception of personal physical appearance, can be positive or negative, leading to body satisfaction or body dissatisfaction. Body satisfaction and dissatisfaction affect individuals of all ages and have the potential to impact lifestyle choices. Objectives: The purpose of this study was to identify the relationship between body image and healthy lifestyle behaviors. Participants: Undergraduate students at a state university in the southeastern United States. Methods: An email was sent, providing a link to an online survey that included: demographic, body image, and screen time questions; the Moderate to Vigorous Physical Activity tool; and the Health Promoting Lifestyle Profile II. Results: 1,056 usable surveys were returned. The participants were primarily Caucasian females (75%) who were college juniors or seniors (65.5%). The majority (71%) indicated they were satisfied with their body, although many (60.3%) wanted to alter it. Most (65.1%) had a normal BMI. Only 23.3% meet physical activity guidelines. Healthy lifestyle behaviors were engaged in “sometimes” and “often, but not routinely.” Body image was correlated with healthy lifestyle behaviors. Conclusions: Programs and resources focusing on promotion of positive body image, appropriate physical activity, and healthy eating behaviors should be the norm on college campuses.